Políticas públicas de atenção à primeira infância: estudo comparado entre o Programa Criança Feliz e o Programa Primeira Infância Melhor - Ventura, Tatiana Becker (2022)
The present study aimed to carry out a comparative study between the policies of the Happy Child Program (PCF) and the Best Early Childhood Program (PIM) in the State of Rio Grande do Sul. In the theoretical framework, the main conceptual strands and theories about the theme of early childhood for human development were presented, national and international programs were addressed regarding public policies that help in the development of early childhood and, finally, comparison models to evaluate the public policies of the Programa Criança Feliz e Primeira Infância Melhor, emphasized by the Scriven (2007) model. As for the method, the study was characterized as a descriptive field research, applied, with a qualitative approach, carried out with the coordinators of the PCF and PIM programs. Data were collected through two individual semi-structured interviews, in addition to document analysis. In order to analyze the data, Content Analysis based on Bardin (2016) was applied, aiming, through these systematic procedures, to highlight the most important and relevant excerpts from the interviews. The main results showed that although both programs target early childhood, they presented different criteria for adherence, origin and resources. In the PCF, it was observed that the criteria are established by the Ministry of Health, with its origin being Federal, while in the PIM, they are established by the State. Furthermore, it was proven that, in general, both programs had compatible instruments to measure the evaluation of process and results. As for the general importance of the programs, it was possible to see a direct link between the PCF and PIM, especially with regard to comprehensive child development, as well as cognitive, behavioral and health development, with the family as one of the main focuses of the program, in addition to the child. From the perspective of the PCF and PIM Coordinators, it was evident that both programs complement each other, as they work with the same look at both health, assistance and education, which allows their actions to be developed together with the same bias.